Feeding Ecology of the Relict Fish Gymnocharacinus-Bergi, a Characid from Southern South-America - Escalante, Alicia H. (1999)
Fil: Escalante, Alicia H.. Universidad Nacional de Mar del Plata. Mar del Plata; Argentina